2021
DOI: 10.1016/j.apnr.2021.151509
|View full text |Cite
|
Sign up to set email alerts
|

Health-care professionals coping responses to the COVID-19 pandemic in Pakistan

Abstract: Background In the last two years, the infectious disease such as COVID-19 create a prodigious uncertainty not only in general population but also in health care professionals. This often leads to emotional distress in general public and particularly in health care professionals. Objectives During COVID-19 pandemic in Pakistan, the health care professionals experienced unusual stressors. This study aimed to examine the coping responses, optimism, pessimism and psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…Our findings are alarming– not only were healthcare workers facing the risk of exposure and mortality to COVID-19 12 along with unprecedented levels of violence during the pandemic 13 but recent policies by the current government 14 , 15 may drive this low level of trust even further down, leading to a worsening shortage of adequately trained healthcare workers, particularly male healthcare workers, similar to the respondents in our survey, who are leaving clinical medicine in Pakistan to better employment opportunities in the Global North, 16 , 17 worsening quality of clinical care in the country. Similar to our study, another study from Pakistan found that males have more optimism and better coping mechanisms towards the pandemic than females, 18 suggesting that female healthcare workers may be more vulnerable than previously thought. Poor patient compliance is also a driver of growing dissatisfaction with the health care system, given the low literacy in Pakistan and with even lower health literacy rates among the economically disadvantaged population, 19 , 20 served mostly by the government sector hospitals, who already struggle with resource allocation and human resource management.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are alarming– not only were healthcare workers facing the risk of exposure and mortality to COVID-19 12 along with unprecedented levels of violence during the pandemic 13 but recent policies by the current government 14 , 15 may drive this low level of trust even further down, leading to a worsening shortage of adequately trained healthcare workers, particularly male healthcare workers, similar to the respondents in our survey, who are leaving clinical medicine in Pakistan to better employment opportunities in the Global North, 16 , 17 worsening quality of clinical care in the country. Similar to our study, another study from Pakistan found that males have more optimism and better coping mechanisms towards the pandemic than females, 18 suggesting that female healthcare workers may be more vulnerable than previously thought. Poor patient compliance is also a driver of growing dissatisfaction with the health care system, given the low literacy in Pakistan and with even lower health literacy rates among the economically disadvantaged population, 19 , 20 served mostly by the government sector hospitals, who already struggle with resource allocation and human resource management.…”
Section: Discussionsupporting
confidence: 89%
“…Um estudo realizado durante a primeira onda da pandemia, com profissionais de saúde, utilizou-se dos mesmos termos para classificar as estratégias de coping utilizadas por esses trabalhadores 10 . O coping focalizado no problema pode ser entendido O enfrentamento aponta para um conjunto de possibilidades que o indivíduo possui como recurso e não necessariamente atitudes reconhecidas como positivas dentro da situação.…”
Section: Introductionunclassified